“Exploring Light’s Bend: Gravity’s Influence Versus Refraction” (London Journal of Research In Humanities and Social Sciences, 2024)
In this text, we discuss Einstein’s theory of relativity, which has been challenged several times but has only become more solid and confirmed with each attempt to invalidate it, even in contemporary times. In this article, we present one of the arguments that tries to refute the theory and explain why it is incorrect. We aim to present this simply so a wide audience can easily understand.